Teaching Recovery Techniques: evaluation of a group intervention for unaccompanied refugee minors with symptoms of PTSD in Sweden - Sarkadi, Anna; Ådahl, Kajsa; Stenvall, Emma; Ssegonja, Richard; Batti, Hemrin; Gavra, Parthena; Fängström, Karin; Salari, Raziye (European Child & Adolescent Psychiatry, 2018)
In 2015, a total of 35,369 unaccompanied refugee minors (URMs) sought asylum in Sweden. In a previous study of 208 URMs, we found that 76% screened positive for PTSD. This study aimed to (1) evaluate the indicated prevention program Teaching Recovery Techniques (TRT) in a community setting and describe the program’s effects on symptoms of PTSD and depression in URMs; and (2) examine participants’ experiences of the program. The study included 10 groups. Methods for evaluation included the Children’s Revised Impact of Event Scale (CRIES-8) and the Montgomery–Åsberg Depression Rating Scale Self-report (MADRS-S) at baseline and at post-intervention. Qualitative interviews were conducted with 22 participating URMs to elicit their experiences. Pre- and post-measures were available for 46 participants. At baseline, 83% of the participants reported moderate or severe depression and 48% suicidal ideation or plans. Although more than half (62%) of the participants reported negative life events during the study period, both PTSD (CRIES-8) and depression (MADRS-S) symptoms decreased significantly after the intervention (p = 0.017, 95% CI − 5.55; − 0.58; and p < 0.001, 95% CI − 8.94; − 2.88, respectively). The qualitative content analysis resulted in six overall categories: social support, normalisation, valuable tools, comprehensibility, manageability, and meaningfulness when the youth described their experiences of the program, well reflecting TRT’s program theory. Overall, results indicate that TRT, delivered in a community setting, is a promising indicated preventive intervention for URMs with PTSD symptoms. This successful evaluation should be followed up with a controlled study.
Created from Fastlane, Scopus look-up
Keywords: Depression; Prevention; PTSD; Teaching Recovery Technique (TRT); Unaccompanied refugee minors